Identification of a small thrombus in the left ventricle identified on iodine maps derived from dual-source photon-counting detector CT - Masaya Kisohara, MD, PhD; Nobuo Kitera, MSc; Toshihide Itoh, PhD; Kazuma Murai, MD; Akio Hiwatashi, MD, PhD; Tatsuya Kawai, MD, PhD (Radiology Case Reports, 2024)
Transthoracic echocardiography is the main imaging modality to diagnose left ventricular thrombus (LVT), but its efficacy in certain cases is suboptimal. We report a patient in whom an LVT, initially unidentified by transthoracic echocardiography, was successfully diagnosed with iodine maps derived from dual-source photon-counting detector CT (DS-PCD-CT). The 64-year-old male was admitted to our institution following myocardial infarction. Although TTE failed to detect this small LVT, iodine maps derived from CT angiography (which was conducted to evaluate the coronary artery stenosis) revealed its presence. Iodine maps derived from DS-PCD-CT collecting data with high temporal resolution are beneficial to diagnose LVTs.